The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1755-3768.2011.02345.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel OTX2 mutation associated with congenital anophthalmia and microphthalmia in a Han Chinese family

Abstract: graphs and OCT images for grading and the limited number of participants. Epidemiological studies in old age often have problems with a low participation rate. While the age distribution was representative, there could be a bias towards more healthy and mobile persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…There is strong evidence that anophthalmia and microphthalmia have a substantial and overlapping genetic component. Recent studies indicate that ~50% of patients have mutations in several genes including but not limited to SOX2 , OTX2 , and PAX6 (You et al, ). Much less is known about nongenetic risk factors for anophthalmia and microphthalmia (Plaisancie, Calvas, & Chassaing, ; Williamson & FitzPatrick, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that anophthalmia and microphthalmia have a substantial and overlapping genetic component. Recent studies indicate that ~50% of patients have mutations in several genes including but not limited to SOX2 , OTX2 , and PAX6 (You et al, ). Much less is known about nongenetic risk factors for anophthalmia and microphthalmia (Plaisancie, Calvas, & Chassaing, ; Williamson & FitzPatrick, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that anophthalmia and microphthalmia may have a substantial and overlapping genetic component. Recent studies indicate that approximately 50% of patients have mutations in more than 20 genes, including but not limited to, SOX2, OTX2, and PAX6 (6). Much less is known about nongenetic risk factors for anophthalmia and microphthalmia (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…For him, a mutation of the genes NF1, PAX6, SOX2 would be responsible for anophthalmia or microphthalmia. You [18] described a mutation of the OTX2 gene associated with anophthalmia and congenital microphthalmia in a Chinese family. Veronica [19] observed, in one patient, a mutation of the RAX2 gene responsible for unilateral anophthalmia.…”
Section: Discussionmentioning
confidence: 99%